2019
DOI: 10.1097/naq.0000000000000370
|View full text |Cite|
|
Sign up to set email alerts
|

Compassion Fatigue and Compassion Satisfaction Among Multisite Multisystem Nurses

Abstract: Compassion fatigue is a phenomenon that might affect nurses of all specialties. Compassion fatigue occurrence could be profound and costly. The immediate impact could be disruption of the unit culture. This study investigated the prevalence and individual-level factors associated with compassion fatigue among nurses. An upsurge in patients' complexity today may leave nurses stressed with increasing practice demands and vulnerable to compassion fatigue. If ignored, compassion fatigue may compromise nurses' heal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
30
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 14 publications
3
30
1
Order By: Relevance
“…Although it was determined in the study that there was no difference between the unit worked and the level of compassion, in some studies, it was found that the level of compassion fatigue was higher in nurses working in the following units: primary healthcare [11], emergency [9], and intensive care [28]. In addition, it was determined that the compassion level of nurses with high professional satisfaction was higher [8].…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Although it was determined in the study that there was no difference between the unit worked and the level of compassion, in some studies, it was found that the level of compassion fatigue was higher in nurses working in the following units: primary healthcare [11], emergency [9], and intensive care [28]. In addition, it was determined that the compassion level of nurses with high professional satisfaction was higher [8].…”
Section: Discussionmentioning
confidence: 98%
“…In their studies carried out with operating room nurses and in their studies conducted with nurses working in different clinics, Çınar and Aslan [25] and Duarte et al [27], respectively, found that the compassion levels of the nurses were above average. Additionally, in several studies conducted in Turkey and other countries, it was found that the compassion levels of the nurses were at medium levels [1,28]. In a meta-analysis study, on the other hand, the prevalence of compassion fatigue in nurses was reported as 47.6% and it was emphasized that it was high [29].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Levels of burnout and secondary traumatic stress have been found to be higher in nurses than other health practitioners, such as physicians, social workers, and palliative care professionals ( Cavanagh et al, 2020 ). Intensive care unit nurses have been found to experience higher levels of burnout and secondary traumatic stress than either ward nurses ( Kawar et al, 2019 ) or oncology nurses ( Mooney et al, 2017 ). Higher compassion satisfaction has been significantly associated with better physical and mental health ( Fu et al, 2018 ), whereas higher levels of burnout and secondary traumatic stress have been significantly associated with poor physical and mental health ( Fu et al, 2018 ; Ruiz-Fernández et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…7,[16][17][18][19][20][21] In the national field, a scale directly related to stress experienced by nurses has not been encountered in the literature, and the existing scales mostly cover education period of nursing students such as nursing education stress scale, 22 perceived stress scale. 23 The current national and international studies specific to stress in nurses report that the stress experienced in the nursing profession with human contact is intense 20,24 ; it decreases job satisfaction, it causes fatigue, burnout and depression and stress-related diseases 25,26 ; and it is necessary to take measures quickly by determining the level of stress regardless of the unit the nurses work. [27][28][29] Since nursing is a unique profession and has different aspects from other disciplines, the stress experienced should be evaluated more comprehensively and in detail.…”
mentioning
confidence: 99%